Bulungan-Lebak Road Service Period, Jepara Regency Post Repair - Yayan Adi Saputro (PT FORMOSA CENDEKIA GLOBAL, 2023)
Traffic volume is one of the causes of road damage. With the increasing number of vehicles, it is possible that the road will be damaged in a relatively short time. The purpose of this study was to determine the service life of the road and the relationship between vehicle volume and the level of road damage on the Bulungan-Lebak road section. In this study, researchers used visual methods to see the type of damage and then measured the damaged road sections and counted the number of vehicles during peak hours and obtained road age data. In this way, 3 (three) data are obtained, namely road inventory data, damage value data and time data after the last road was repaired